Frac Sand Facilities and Their Potential Effects on the Groundwater Resources of the Monahans-Mescalero Sand Ecosystem, Permian Basin, Texas - Robert Mace; Chelsea Jones (Texas Water Journal, 2023)
Up until the end of the oil and gas boom in 2014, much of the sand used in the Permian Basin for hydraulic fracturing was sourced from upper Midwest of the United States. Because of substantial cost savings, producers in the Permian Basin began using local sand resources, creating an associated boom in local frac-sand mining in the Monahans-Mescalaro Sand Ecosystem. By December 2018, 17 frac-sand operations had registered with the Texas Commission on Environmental Quality with 16 being operational with a cumulative annual capacity of 56.8 million tons and a self-reported 2,927 acres of disturbed land. We identified 230 production wells for the 16 facilities with depths ranging from 80 to 1,199 feet and most completed in the Pecos Valley Alluvium and/or Dockum aquifers. Estimated frac sand facility water use (10,000 to 40,000 acre-feet per year, based on 60 to 250 gallons of water consumed per ton of produced sand) rivals or exceeds that of water used in the four counties (Crane, Ector, Ward, and Winkler) with active frac sand facilities (23,500 acre-feet per year). Modeling suggests that long-term pumping of the unconfined Pecos Valley Aquifer may be a challenge requiring additional wells over time or the use of alternative water supplies. For the confined Dockum Aquifer, simulations suggest that pumping might completely deplete artesian pressure at the well field after 10 years.